Noumenal power revisited: reply to critics. Issue 3 (2nd September 2018) - Forst, Rainer
ABSTRACT: In this reply to critiques by Albena Azmanova, Pablo Gilabert, Mark Haugaard, Clarissa Rile Hayward, Matthias Kettner, Steven Lukes, and Simon Susen, Rainer Forst explains and expands upon his theory of 'noumenal power.' In particular, he stresses the non-normative character of the approach and clarifies how the account of the exercise of power as working through 'giving' reasons also includes non-reflexive and non-transparent forms of producing reasons in others. This has implications for aspects of power that relate to the unconscious, the body and for understanding ideological as well as structural power.